Sistema de melhoria organizacional com base na avaliação de desempenho - Kall, Elenice (2014)
Improvement systems are being used with greater frequency in recent decades in order to increase market competitiveness. The intention to focus the study on a system -based improvements in performance assessment meets proposes a measurement of the action plans of this system. For making improvements in a process involves not only concepts and tools, but also the measurement methodology to diagnose the actions taken during the project implementation. The study was conducted in the industry CVI Refrigerants Ltd, franked by The Coca - Cola Company and Heineken Brazil with factory in Santa Maria and distribution centers in Passo Fundo Santa Cruz and South To implement an evaluation model on a plan improvements that is being proposed, we used the fourth step of the model proposed by Siluk (2007 ) - Performance , characterized by continuous improvement , personal and organizational process. In order to quantify this tool we used models of correlation and linear regression - time series, proposing a model of organizational improvement system for two quality attributes in a soft drink industry - carbonation and torque. The expectation is that the improvements implemented in each area will yield results for any company or other franchised Coca Cola System. The main results were obtaining first place in the attribute of torque and second place in the ranking attribute carbonation Coca Cola Brazil.